1998
DOI: 10.2190/gcgw-86dc-a30r-286a
|View full text |Cite
|
Sign up to set email alerts
|

Post-Homicide Reactions: Grief, Mourning and Post-Traumatic Stress Disorder following a Drunk Driving Fatality

Abstract: This article examines the impact of gender, religious beliefs, subjective health status, individuals' past experience with death, social support, and time since the death on the extent of mourning, the extent of grieving, and Post-traumatic Stress Disorder (PTSD) symptomatology. It is proposed that the mode of death complicates the nature and course of bereavement after the death of a primary family member in a drunk driving collision. The unnecessary and violent nature of the death of drunk driving victims ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 9 publications
0
29
0
Order By: Relevance
“…Further, those in the bereaved sample were either native English speakers or highly competent in English, meaning that the experiences of people from culturally and linguistically diverse backgrounds might not be represented adequately in the data. Samples of other research projects on the psychosocial outcomes of crash fatalities have been drawn either from activist groups (e.g., Federation of European Road Traffic Victims, 1993Victims, , 1995Lord, 1987;Tehrani, 2004), or mutual-help groups (e.g., Spooren et al, 2000Spooren et al, -2001Sprang & McNeil, 1998), or the wider community (e.g., Lehman et al, 1989;Shanfield & Swain, 1984). Sampling from four sources (a mutual-help group, an activist group, community newspapers, and snowballing from informants) reduced the likelihood that the sample, and therefore the data, is prejudiced, and thus confidence in a relatively representative sample is high.…”
Section: Resultsmentioning
confidence: 99%
“…Further, those in the bereaved sample were either native English speakers or highly competent in English, meaning that the experiences of people from culturally and linguistically diverse backgrounds might not be represented adequately in the data. Samples of other research projects on the psychosocial outcomes of crash fatalities have been drawn either from activist groups (e.g., Federation of European Road Traffic Victims, 1993Victims, , 1995Lord, 1987;Tehrani, 2004), or mutual-help groups (e.g., Spooren et al, 2000Spooren et al, -2001Sprang & McNeil, 1998), or the wider community (e.g., Lehman et al, 1989;Shanfield & Swain, 1984). Sampling from four sources (a mutual-help group, an activist group, community newspapers, and snowballing from informants) reduced the likelihood that the sample, and therefore the data, is prejudiced, and thus confidence in a relatively representative sample is high.…”
Section: Resultsmentioning
confidence: 99%
“…The similar constructs of grief, mourning, and extent of grief difficulties, were each significantly crosssectionally associated with social support in two separate exploratory studies [36,44], both with a low risk of bias.…”
Section: Other Psychological Wellbeing Outcomes (Eight Studies)mentioning
confidence: 88%
“…Four other studies [34,36,38,41] found a positive association between social support and PTSD. Two of these studies [34,38,41] had a medium risk of bias and one [36] had a low risk.…”
Section: Ptsd (Six Studies)mentioning
confidence: 88%
“…A recent prospective, longitudinal study of primary caregivers who lost a family member to cancer found that a composite measure of religious beliefs and activities was related to less Religion and Spirituality in Adjustment 715 depression 13 months post-loss, controlling for baseline depression, age, caregiver burden, and restriction on activities (Fenix et al, 2006). Similarly, in a study of adults who had lost a family member to a drunk driving accident, despite a wide range in time post-loss (one month to over five years), religious beliefs and behaviors were related to less mourning post-loss and current grieving and to fewer PTSD symptoms, even when controlling for social support, subjective health status, gender, race, and marital status (Sprang & McNeil, 1998).…”
Section: Composite Beliefs and Activitiesmentioning
confidence: 98%